Beta Cell Dysfunction and Insulin Resistance - Cerf, Marlon E. (Frontiers in Endocrinology, 2013)
Beta cell dysfunction and insulin resistance are inherently complex with their interrelation for triggering the pathogenesis of diabetes also somewhat undefined. Both pathogenic states induce hyperglycemia and therefore increase insulin demand. Beta cell dysfunction results from inadequate glucose sensing to stimulate insulin secretion therefore elevated glucose concentrations prevail. Persistently elevated glucose concentrations above the physiological range result in the manifestation of hyperglycemia. With systemic insulin resistance, insulin signaling within glucose recipient tissues is defective therefore hyperglycemia perseveres. Beta cell dysfunction supersedes insulin resistance in inducing diabetes. Both pathological states influence each other and presumably synergistically exacerbate diabetes. Preserving beta cell function and insulin signaling in beta cells and insulin signaling in the glucose recipient tissues will maintain glucose homeostasis.